Streptomyces venezuelae NRRL B-65442: genome sequence of a model strain used to study morphological differentiation in filamentous actinobacteria. (8th June 2021) - Gomez-Escribano, Juan Pablo; Holmes, Neil A; Schlimpert, Susan; Bibb, Maureen J; Chandra, Govind; Wilkinson, Barrie; Buttner, Mark J; Bibb, Mervyn J
Abstract: For over a decade, Streptomyces venezuelae has been used to study the molecular mechanisms that control morphological development in streptomycetes and is now a well-established model strain. Its rapid growth and ability to sporulate in a near-synchronised manner in liquid culture, unusual among streptomycetes, greatly facilitates the application of modern molecular techniques such as ChIP-seq and RNA-seq, as well as time-lapse fluorescence imaging of the complete Streptomyces life cycle. Here we describe a high-quality genome sequence of our isolate of the strain (Northern Regional Research Laboratory [NRRL] B-65442) consisting of an 8.2 Mb chromosome and a 158 kb plasmid, pSVJI1, which had not been reported previously. Surprisingly, while NRRL B-65442 yields green spores on MYM agar, the American Type Culture Collection (ATCC) type strain 10712 (from which NRRL B-65442 was derived) produces grey spores. While comparison of the genome sequences of the two isolates revealed almost total identity, it did reveal a single nucleotide substitution in a gene, vnz_33525, involved in spore pigment biosynthesis. Replacement of the vnz_33525 allele of ATCC 10712 with that of NRRL B-65442 resulted in green spores, explaining the discrepancy in spore pigmentation. We also applied CRISPR-Cas9 to delete the essential parB of pSVJI1 to cure the plasmid from the strain without obvious phenotypic consequences.